2016
DOI: 10.1308/rcsann.2016.0049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a dedicated emergency surgical unit on early laparoscopic cholecystectomy for acute cholecystitis

Abstract: INTRODUCTION Emergency general surgery (EGS) accounts for 50% of the surgical workload, and yet outcomes are variable and poorly recorded. The management of acute cholecystitis (AC) at a dedicated emergency surgical unit (ESU) was assessed as a performance target for EGS. METHODS The outcomes for AC admissions were compared one year before and after inception of the ESU. The impact on cost and compliance with national guidance recommending early laparoscopic cholecystectomy (ELC) within seven days of diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…There is good evidence that dedicated EGS surgeons can improve a variety of outcomes for patients with appendicitis [11,12] and gallstone disease [12][13][14][15]. However, a number of papers in the literature express concern about the outcomes of more specialized procedures, particularly colorectal resection [16][17][18][19][20][21] and gastrectomy [22].…”
Section: Introductionmentioning
confidence: 99%
“…But the exact time point of ELC in AC is still a matter of debate. Tokyo Guidelines 2013 preferred to perform LC within 72 hours of symptom onset 6 , whereas NICE recommended LC in AC within 7 days of diagnosis 7 . Till now there is no published document on LC beyond 7 days of onset of AC.…”
Section: Discussionmentioning
confidence: 99%
“…pancreatic surgery suggested that emergency cholecystectomy was indicated for patients with symptoms within 72 hours while that of the national institute for health and care excellence (NICE) recommended that AC should be treated within seven days of diagnosis 7 .…”
mentioning
confidence: 99%